Análise da micro e minigeração fotovoltaica no município de Campo Mourão no período de 2016 a 2023 - Corrêa, Fabiana Costa (2023)
Throughout history, the use of energy has become increasingly essential in everyone's life. The almost constant growth of the world population poses one of the great challenges today, given the uncertainty about the future availability of energy in the face of demand, primarily due to the high scale of exploitation of non-renewable resources provided by the planet. In light of this reality, there is an increasing need to explore alternative sources of electricity generation. The main renewable energy sources used in Brazil include hydro, biomass, solar, and wind, with geothermal and ocean energy also being considered. In this context, distributed generation has become a relevant topic, as it offers an alternative way for consumers to reduce their electricity tariffs. Among the sources that have gained prominence, photovoltaic solar generation has expanded exponentially. As a result, there has been a notable increase in the number of distributed micro and mini-generation systems connected to the grid. This growth has raised concerns among agencies in the distribution sector. Consequently, there was a need to establish the distributed micro and mini-generation market through federal law, leading to the approval of Law 14.300/2022. This law establishes the legal framework for distributed microgeneration and minigeneration in the country. This work aims to analyze the installed capacity of distributed generation photovoltaic solar energy systems in the municipality of Campo Mourão, examining the effects of the changes resulting from Law 14.300/2022. To achieve the general objective, the database of the National Electric Energy Agency was used. In the results, it was observed that the consumption modality with the highest number of generating units and amount of installed power inserted in the period from 2016 to 2023 was the generation in the consumer unit itself for the Residential consumption class. It was also observed that in relation to powers, between 2016 and 2022 the Industrial and Rural classes were considerably larger, but with smaller numbers when it comes to distributed generating units. And it is concluded that there was a deceleration in 2023 regarding the growth in the number of generating units and installed power in the municipality of Campo Mourão.